The features of deformation-stimulated RbI luminescence - Myasnikova, L; Maratova, A.G.; Shunkeyev, K.Sh. (Eurasian Journal of Physics and Functional Materials, 2026)
This paper studies deformation-stimulated features of radiative relaxation of self-trapped excitons and recombination assembly of exciton-like luminescence in RbI crystal. Methods of research were luminescence and thermal activation spectroscopy. The identity of the mechanism of manifestation of the X-ray luminescence, tunnel luminescence and thermally stimulated luminescence spectra were found in the elastically deformed RbI crystal, interpreted by the luminescence of self-trapped exciton, tunnel recharge of F′, VK -pairs and thermally stimulated recombination of e−, VK -centers, respectively. The temperatures of the maximum destruction peaks of thermally stimulated luminescence, their spectral composition and activation energies were determined experimentally, on the basis of which the mechanisms of recombination assembly of exciton-like luminescences in a RbI crystal were interpreted. Uniaxial elastic deformation leads to the effective formation of point radiation defects ( F′, HA, VK-centers) in comparison with an unbroken lattice, where the predominant mechanism is the association of interstitial atoms ( H -centers) with the formation of (Formula presented) -centers. © 2021. All Rights Reserved. Recommended Citation Myasnikova, L. N.; Maratova, A. G.; and Shunkeyev, K. S. (2021) "The features of deformation-stimulated RbI luminescence," Eurasian Journal of Physics and Functional Materials: Vol. 5: No. 4, Article 6. DOI: https://doi.org/10.32523/ejpfm.2021050406